Inequality and transaction costs in a community-based water supply in rural area adjacent to national park - Ambar Istiyani; Mohamad Shohibuddin (Publisher of Widyagama University of Malang (UWG Press), 2021)
National parks can be sensitive state-property areas since the surrounding communities generally need the parks' resources for their livelihood. This paper focuses on inequality and transaction costs in PAMSIMAS (Community-Based Water Supply and Sanitation), a water sector program in Indonesia’s rural and peri-urban areas. The method used is a case study of PAMSIMAS in Tajuk, a village adjacent to Mount Merbabu National Park in Semarang Regency, Central Java. The data were gathered from documentary studies, in-depth interviews, and observations, and were analyzed using transaction cost economics and institutional analysis. This study found that the rules of PAMSIMAS, especially water pricing mechanisms, enhanced water availability but could not diminish the uncertainty of water access and transaction costs born by water users. Inequalities of endowment, power, and information among the hamlets affected how PAMSIMAS was run. Mobilization of water resources is related to property rights, which should be well-defined. Still, there was an overlapping property institution of Mount Merbabu National Park forest and its water resources; thus, the water user groups had to bear different transaction costs. The study provides suggestions for providing broader 'rules of the game' in rural water management, recognizing local conditions and prospects, acknowledging community rights to resources, and developing inclusive community participation.JEL Classification D23; P48; Q15